Emerging Trends in International Tourism - Dr. Anupa Singh (International Journal of Engineering and Management Research, 2019)
Travel and tourism has many positive benefits, including that it is for many countries, the main source of job creation and revenue (Pender and Sharpley, 2005).Tourism provides around 9 to 10% of the world’s jobs and millions more indirectly via the multiplier effect in other sectors from construction to agriculture or telecommunications. Also tourism accounts for 30% of the world’s exports of services (US$ 1 trillion a year) and is the top export category in developing countries(World Tourism Organization, 2018).In 2012, the tourism industry reached an historical point with one billion international arrivals in one year for the first time according to World Tourism Barometer (2013). International Tourist arrivals increased from 25 million in 1950 to 1,326 million in 2017 whereas international tourism receipts increased from 2 billion US$ in 1950 to US$ 1,340 billion in 2017. In 2017, Travel and Tourism’s total economic contribution represented 10.4% of total GDP, 4.5% of total Investments and 6.5% of world exports. Taking in considerations these facts, the paper presents the evolution of the international tourism in the world analyzing the trends and the economic implication. It also highlights the major emerging trends affecting the global tourism industry – Millennials, rise of Chinese tourists, increased terrorist attacks, rise of cruise holidays, advances in information technology, investment in tourist sites, enhanced transportation, active and adventure trips, female solo travel, food tourism, responsible tourism and mobile photography. The opportunities, challenges and implications posed by them are also discussed.